Watermark resynchronization: an efficient approach based on eulerian tours around a robust skeleton - Raftopoulos, Konstantinos; Ntalianis, Klimis S.; Tzouveli, Paraskevi K.; Tsapatsoulis, Nicolas; Parker-Wood, Aleatha; Ferecatu, Marin (My University, 2013)
The existing block-based approaches, albeit successful in resisting frequency domain attacks, are sensitive to geometric distortions due to the lack of reference in repositioning the block grid. In this paper an RST-invariant block-based approach is proposed, aiming at protecting image objects. The term “image object” refers to semantically contiguous parts of images that have a specific contour boundary. The proposed approach is based on shape information, since the watermark is embedded in image blocks, the location and orientation of which are defined by Eulerian tours that are appropriately arranged in layers, around an object’s robust skeleton. Images from the Polymathic project are used to illustrate the technique.
Keywords: Object-based watermarking; Resynchronization; Skeleton transform; Global-Local transformation; Eulerian tours